Local elections 1966 - Westerståhl, Jörgen (University of Gothenburg, 1982)
The project ´Local government autonomy - local government boundaries´ was carried out jointly by the Departments of Political Science at five Swedish universities. It was conducted from 1965 to 1971, on the eve of the comprehensive amalgamations of municipalities which had been decided on but not fully implemented. This study, carried out in connection with the local elections in 1966, embraces 50 personal interviews in each of the 36 municipalities of sample A and 200 personal interviews in each of the three largest cities, making a total of 2 400 interviews. The interview questions deal with, among other things, duration of residence, experience of other types of municipalities, knowledge about and attitude toward local self-government, party activity, and evaluation of local government services.

Studien har utförts som en del i projektet ”Den kommunala självstyrelsen”, ett samarbete mellan statsvetenskapliga institutioner vid fem svenska universitet 1965-1971, strax innan den omfattade kommunsammanslagningen som verkställdes 1971
Studien genomfördes i samband med det lokala allmänna valet 1966 och genomfördes i två steg, dels intervjuades invånare i 36 kommuner och dels gjordes intervjuer med invånare i var och en av de största städerna. Totalt 2 400 intervjuer som bland annat innehåller frågor om medborgarnas kunskaper och inställning till kommunalt självstyre, partitillhörighet, åsikter och erfarenheter av kommunala tjänster samt erfarenheter från andra kommuner.
Kommunala valrörelser 1966
Keywords: internal politics; inrikespolitik; Political behaviour and attitudes; Politiska beteenden och attityder; Elections; Val; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap